Maternal mortality ratio in selected rural communities in Kebbi State, Northwest Nigeria - Usman Gulumbe; Olatunji Alabi; Olusola A. Omisakin; Semeeh Omoleke (BMC, 2018)
Abstract Background Maternal mortality remains a topical issue in Nigeria. Dearth of data on vital events posed a huge challenge to policy formulation and design of interventions to address the scourge. This study estimated the lifetime risk (LTR) of maternal death and maternal mortality ratio (MMR) in rural areas of Kebbi State, northwest Nigeria, using the sisterhood method. Methods Using the sisterhood method, data was collected from 2917 women aged 15-49 years from randomly selected rural communities in 6 randomly selected local government area of Kebbi State. Retrospective cohort of their female siblings who had reached the childbearing age of 15 years was constructed. Using the most recent total fertility rate for Kebbi State, the lifetime risk and associated MMR were estimated. Result A total of 2917 women reported 8233 female siblings of whom 409 had died and of whom 204 (49.8%) were maternal deaths. This corresponds to an LTR of 6% (referring to 11 years before the study) and an estimated MMR of 890 deaths/100,000 live births (95% CI, 504-1281). Conclusion The findings provide baseline information on the MMR in rural areas of the State. It underscores the need to urgently address the bane of high maternity mortality, if Kebbi State and Nigeria in general, will achieve the health for all by year 2030 as stated in the Sustainable Development Goals (SDGs).